Business advisory system / Cheong Bon Tsong - Cheong , Bon Tsong (2004)
Business Advisory System (BAS), as the name suggest, is an advisory system in the world of business. Since the business domain is so huge, this project will only focus on the area of Human Resources Management to provide 4 major services: recruitment, selection, retrenchment and salary cut down. Although BAS is a standalone system, it is able to communicate with other web application through web services. It basically receives inputs either forms the user or the web application mentioned and provides advice to the user. The major objective of BAS is for complying the company's objective, which is maximize the profit and minimize the cost. While other objectives are to reduce the heavy workload of HR staffs and help in decision making especially at the management level when recruitment and retrenchment occur. The problem solving approach used in BAS is Case-based Reasoning (CBR). CBR is an intelligent reasoning methodology used to solve problem based on the past cases stored in a case library (Kolodner, 1993). CBR's concept is to solve a new case by retrieving a similar case from the case library and adapting the solution for the new case.